EFEKTIVITAS KEBIJAKAN RELOKASI PASAR JOHAR KOTA SEMARANG - Desvara, Zahira; Maesaroh, Maesaroh (Journal of Public Policy and Management Review, 2024)
The Semarang City Government established the policy for relocating Johar Market through Mayor Regulation No. 19 of 2021 concerning Procedures for Placing Traders from the Former Johar Market Area Post-Revitalization. The implementation of the relocation policy is suspected to have not been executed properly due to several issues leading the Johar Market Traders Association to demand a restructuring. This study aims to analyze the effectiveness of the policy and the factors influencing the implementation of the Johar Market relocation policy in Semarang City. In this research, qualitative research methods were utilized with data collection techniques including interviews, observations, and documentation. The results of this study indicate that the Johar Market relocation policy in Semarang City is running less effectively due to constraints in terms of policy accuracy, implementation accuracy, and target accuracy dimensions, although the environmental accuracy dimension is functioning well. There are supporting factors for the implementation of the Johar Market relocation policy, such as communication, resources, and bureaucratic structure, while inhibiting factors for the implementation of the policy include disposition factors.